2019
DOI: 10.5539/jas.v11n15p1
|View full text |Cite
|
Sign up to set email alerts
|

Grain Quality and Yield of Rice in the Main and Ratoon Harvests in the Southern U.S.

Abstract: The ratoon rice system is an energy-saving, high-efficiency cultivation method. Harvests from a two-year field trial with a main crop (MC) and a ratoon crop (RC) were used to evaluate milled grain quality traits and yield performance. The results indicated that chalkiness was significantly lower in the RC than in the MC. Chalkiness ranged from 1.90 to 15.01%, with an average of 6.46%, in the MC and from 0.66 to 3.28%, with an average of 1.50%, in the RC across two years. In addition, nearly all of the RC of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The milling quality is an important index affecting the economic value of rice, including brown rice rate, milled rice rate, and head milled rice rate [37]. Previous studies showed a positive correlation between the milled rice rate and yield, but there was no significant correlation between the head milled rice rate and yield [38]. In this study, we found no significant difference in the brown rice rate and milled rice rate across different grain yield types, but the head milled rice rate of the HGY varieties was significantly lower than that of the LGY varieties (Table 6).…”
Section: Rice Quality Characteristics Of Semi-waxy Japonica Rice With...mentioning
confidence: 99%
See 1 more Smart Citation
“…The milling quality is an important index affecting the economic value of rice, including brown rice rate, milled rice rate, and head milled rice rate [37]. Previous studies showed a positive correlation between the milled rice rate and yield, but there was no significant correlation between the head milled rice rate and yield [38]. In this study, we found no significant difference in the brown rice rate and milled rice rate across different grain yield types, but the head milled rice rate of the HGY varieties was significantly lower than that of the LGY varieties (Table 6).…”
Section: Rice Quality Characteristics Of Semi-waxy Japonica Rice With...mentioning
confidence: 99%
“…It has been well documented that chalkiness is controlled by polygenes, resulting from the loose packing of starch granules in the grain endosperm [44,45]. Cai et al [38] suggested that ratoon rice with low grain yield had lower chalkiness than the main crop rice with a high grain yield. In this study, we also found that the average chalky kernel rate, chalky area, and chalkiness degree of the HGY varieties were significantly higher than those of the LGY varieties (Table 6).…”
Section: Rice Quality Characteristics Of Semi-waxy Japonica Rice With...mentioning
confidence: 99%
“…The quality of forage and sweet sorghum also showed differences between the main and ratoon crops ( Rao et al, 2011 ; Vinutha et al, 2017 ). In terms of rice ratooning, extensive research has confirmed a higher rice quality of ratoon crop ( Liu et al, 2002 ; Wu et al, 2019 ), due to a lower chalkiness and white vitreous and a higher milled rice recovery than that of the main crop ( Cai et al, 2019 ). Duan et al (2018) considered that the lower temperature and larger diurnal temperature range during the filling stage might be the reasons for the better quality of grain in the ratoon crop.…”
Section: Discussionmentioning
confidence: 99%
“…Ratoon rice cropping is a green and resource-efficient method for increasing rice production 1,4,9,38 and is therefore currently widely used in South China. 2 Many previous studies have demonstrated that the improvement of rice quality occurred in ratooning season rice as compared to not only its first season cropping rice 10,39 but also late-cropping season rice. 5 Furthermore, rice quality, which varied among main-cropping season rice, ratooning season rice and late-cropping season rice, has been collectively investigated in this study.…”
Section: Discussionmentioning
confidence: 99%